Use of Artificial Intelligence in HR Recruitment and Selection in Start-up Companies - Rovanita Rama; Jasmin Jasmin; Arief Yanto Rukmana; Said Hamzali; Arnes Yuli Vandika (Westscience Press, 2024)
This bibliometric study analyzes the evolving landscape of human resource management (HRM), emphasizing the integration of technology into HR practices, particularly in recruitment and selection processes. Utilizing VOSviewer, the research maps the co-occurrence of keywords within a comprehensive dataset, revealing dominant themes, trends over time, and less explored areas. The analysis identifies core thematic clusters such as